Stay healthy - Donepudi, Sravani (Kansas State University, 2018)
It’s difficult to keep track of sleep patterns, medicine and water intake. Having sufficient sleep every day is very important as not getting enough sleep can lead to difficulties remembering things, concentrating and other problems. This application provides tools to track the sleeping pattern of the user based on the inputs given. When the user picks a date, a weekly graph is generated to see how the user’s sleep cycle looks. It also displays the average hours the user slept each day and the sleep pattern type below the graph. Medicine reminder is another tool which reduces the risk of skipping medicines. As many people tend to complicate the severity level of the disease by forgetting to take the required medicine, this app can help them to prevent such problems. It reminds them to take their medicine at the entered times until the end of the course duration. People often tend to forget to drink enough water. Staying hydrated is very important for our body to function properly and flush out toxins. For this purpose, this app features a water reminder to remind the user to drink water every hour until the daily limit is reached. This is done by calculating the amount of water that should be consumed every day based on the user’s details like age, weight, physical activity and gender. Apart from these, to stay fit and healthy one should do some physical activity every day which helps to activate their body. The instructions and videos of some exercises, information on health tips, and natural remedies to some common health problems that can be cured without any medication are provided in the app. This would be a very convenient application for those who are very busy with their work life and have difficult time tracking their sleep, medicine times and staying hydrated at work.
Keywords: Stay healthy; Health; Android Application; Sravani Donepudi; Mobile app